Non-coding RNAs participate in the regulatory network of CLDN4 via ceRNA mediated miRNA evasion - Yong-xi Song (Nature Portfolio, 2017)
Non-coding RNAs can modify the expression of proteins in cancer networks. Here the authors reveal a regulatory network in gastric cancer whereby claudin-4 expression is reduced by specific miRNAs, which are in turn bound by specific lncRNAs acting as competing endogenous RNAs (ceRNAs), resulting in increased claudin-4 expression.